50 - OVERWEIGHT AND OBESITY IN PUBLIC NETWORK STUDENTS (Fiep Bulletin - online, 2023)
Obesity and overweight are worrying diseases that are characterized by the accumulation of excessive fat and lack of healthy foods and also by the lack of physical activities, all of which are associated with many risks that may come in the future, bringing various health complications. For this reason, this research aims to identify the levels of overweight and obesity in public school children. This descriptive field research involved techniques and devices to perform the procedures. The sample consisted of 67 kindergarten students. To carry out this evaluation, an analog scale with a stadiometer are used. Data is treat quantitatively in Microsoft Excel software for Windows. The results show means and standard deviation in girls (female sex) the following answers. Age 3.9±0.6. Weight 17.4±3.2.  Height 1±0.1 and BMI16.6±2.0.  While for boys (males), the following afound.  age 4.1±0.8.  Weight 18.4±3.5; height 1.0±0.1 and BMI 16.7±2.1, with the result being AGE±SD 4±0.7; WEIGHT±SD 17.9±3.4; HEIGHT±SD 1±0.1 and finally the BMI±SD 17±2.0. It was possible to conclude that the BMI considered relevant for these results and may be associated with inadequate eating habits, lack of physical activity, among other factors, considering the possibility of more comprehensive studies.
Keywords: Obesity. Overweight. Physical activity